Human parasitology - Bogitsh, Burton J.
Human Parasitology, Fifth Edition emphasizes a medical perspective that also incorporates functional morphology, physiology, biochemistry and immunology to enhance appreciation of the diverse implications of parasitism. Bridging the gap between classical clinical parasitology texts and traditional encyclopedic treatises, the book will not only appeal to students interested in the medical aspects of parasitology, but also those who are interested in gaining a solid foundation in the biology of parasites. This updated edition has been fully revised to integrate the most recent molecular discoveries about mosquitoes, ticks and other arthropods as vectors, along with the most effective therapeutic regimens for each.